PELATIHAN PEMBUATAN SOAL EVALUASI PEMBELAJARAN BERBASIS DIGITAL DI ERA DISRUPSI TEKNOLOGI - Maifit Hendriani; Riri Marfilinda; Sry Apfani (Jurnal Abdi Insani, 2022)
The era of technological disruption has had a major impact in all fields. Work and activities that were originally carried out directly and real, in this era turned into virtual with the existence of technology. In the field of education, the era of technological disruption requires educators to constantly innovate by using technology and digital media in the implementation of learning. Plus the impact of Covid-19 which all have to be carried out from home. However, the skills of educators to utilize technology in learning are still low. Especially in carrying out the digital-based learning evaluation process. The purpose of implementing this community service activity is to provide knowledge about the importance of digital literacy in the world of education and training in making digital-based evaluation questions using the live worksheet website. This community service activity is in partnership with SDIT Adzkia 3 Padang. The participants of this community service activity were 22 educators. The methods of this service activity are lectures, demonstrations and simulations as well as direct training assistance. This community service activity has succeeded in providing educators with a new understanding of the importance of digital literacy in the world of education. The results of the assistance in making evaluation questions directly, educators at SDIT Adzkia 3 are able to design evaluation questions using the live worksheet website with multiple choice questions, join arrows, drop down and drag and drop questions and are able to input videos into the evaluation question sheet. during the activities, the training participants seemed enthusiastic about the material presented and were actively involved in activities. The training was successful and went smoothly. The training participants increased their understanding of the importance of using technology in learning and also increased the skills of educators in evaluating and providing new innovations in carrying out learning evaluations at SDIT Adzkia 3.